The Arabs in Early Palembang Darussalam Sultanate: The History and Implication - Ahmad Rofiq; Choirun Niswah; Bety Bety; Maryam Maryam; Rahmat Abdullah (TSAQAFAH, 2025)
This study examines the significant contributions of the Arab community, specifically from Hadramaut, Yemen, to the socio-religious and cultural development of Palembang, Indonesia. The Arab community, primarily Sunni Muslims, arrived during the era of the Palembang Darussalam Sultanate in the 17th century and played a pivotal role in the Islamization of the region and the enrichment of local identity through cultural and social values. This research addresses the reception of Arab-Islamic practices by the local population, which resulted in notable acculturation, evident in religious traditions such as Maulid Nabi and zikr practices, as well as the incorporation of Islamic principles in governance and daily life. The study employs a qualitative methodology with a descriptive approach, relying on in-depth interviews with prominent figures and descendants of the Arab community, as well as an analysis of historical documents, including manuscripts and reports from archaeological sites. It focuses on historical areas like Kampung Arab Al-Munawwar and Ulu-Ilir, which are central to the Arab community’s legacy in Palembang. The findings highlight the establishment of Islamic educational institutions, such as madrasahs and pesantrens, by prominent figures like Habib Alwi Bahsin. These institutions played key roles in disseminating religious and general knowledge, fostering intellectual and social empowerment. Additionally, evidence of the reception of Islamic values into local culture can be found in acculturated traditions, culinary practices, and community activities that go beyond well-known practices like Maulid and zikr. In conclusion, the Arab community’s contributions extend beyond religious propagation, encompassing education, social development, and cultural reception, ultimately shaping Palembang’s identity as a vital center of Islamic civilization in the Nusantara.